Software for Retaining Walls Design - Azzam Allam Naji Alrandi (My University, 2014)
Retaining Walls are structures used to support and retain unstable masses of earth, Due to the huge local Demand for these structure such a convenient, flexible, user-friendly and practical software will be presented, based on new design techniques, Gravity, Cantilever, And Counterfort Retaining walls are considered in Only one software, this software will design for static and seismic conditions. Pseudo-dynamic analysis for seismic design are included in addition to the pseudo static, An option of fully optimization of the dimensions based on artificial intelligence algorithms searches saving nearly from 20 % to 40% of the cost are available, well-organized results by a summary sheet and a graphical detailed section, AutoCAD detailed Drawing, Full Report, Excel, Word Summaries, and pdf results, with the required area of steel, the cost and the layout of bars are provided.